2015
DOI: 10.1073/pnas.1505586112
|View full text |Cite
|
Sign up to set email alerts
|

pH homeostasis during coral calcification in a free ocean CO 2 enrichment (FOCE) experiment, Heron Island reef flat, Great Barrier Reef

Abstract: Geochemical analyses (δ 11 B and Sr/Ca) are reported for the coral Porites cylindrica grown within a free ocean carbon enrichment (FOCE) experiment, conducted on the Heron Island reef flat (Great Barrier Reef) for a 6-mo period from June to early December 2010. The FOCE experiment was designed to simulate the effects of CO 2 -driven acidification predicted to occur by the end of this century (scenario RCP4.5) while simultaneously maintaining the exposure of corals to natural variations in their environment und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
83
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(102 citation statements)
references
References 50 publications
15
83
4
Order By: Relevance
“…Slower growth rates under ocean acidification are therefore presumably attributed to additional energetic costs that require ∼10% per 0.1 units decrease in seawater pH in order to maintain elevated pH values at the site of calcification (McCulloch et al, 2012b). pH homeostasis during calcification was also observed in several tropical shallow-water corals (Hönisch et al, 2004;Krief et al, 2010;Trotter et al, 2011;McCulloch et al, 2012a;Holocomb et al, 2014;Georgiou et al, 2015) but was found to be not as strong as in cold-water corals ( pH between seawater pH T and pH cf ) (McCulloch et al, 2012b), demonstrating the adaptation of these corals to live in environments with naturally lower aragonite saturation states.…”
Section: Growth Ratesmentioning
confidence: 99%
“…Slower growth rates under ocean acidification are therefore presumably attributed to additional energetic costs that require ∼10% per 0.1 units decrease in seawater pH in order to maintain elevated pH values at the site of calcification (McCulloch et al, 2012b). pH homeostasis during calcification was also observed in several tropical shallow-water corals (Hönisch et al, 2004;Krief et al, 2010;Trotter et al, 2011;McCulloch et al, 2012a;Holocomb et al, 2014;Georgiou et al, 2015) but was found to be not as strong as in cold-water corals ( pH between seawater pH T and pH cf ) (McCulloch et al, 2012b), demonstrating the adaptation of these corals to live in environments with naturally lower aragonite saturation states.…”
Section: Growth Ratesmentioning
confidence: 99%
“…One site was selected on the reef crest (Reef Crest, RC), and within the lagoon, three sites were chosen [Reef Flat (RF), Shallow Lagoon (SL), Deep Lagoon (DL)] (Figure 1). The lagoonal study area is shallow and periodically isolated at low tide, resulting in extreme diel fluctuations in seawater conditions (Kinsey and Kinsey, 1967;Potts and Swart, 1984;Georgiou et al, 2015). …”
Section: Study Sitesmentioning
confidence: 99%
“…The southern, offshore reefs were the least affected GBR region from the cumulative footprint of the last three major coral bleaching events (Hughes et al, 2017), and since 1992, have experienced only one major damage-inducing cyclone in 2009 (Connell et al, 1997;Woolsey et al, 2012). Within Heron reef, specific geomorphological zones include a gamut of naturally variable benthic communities subject to distinct diel and seasonal changes in seawater conditions (Phinn et al, 2012;Georgiou et al, 2015). As such, Heron reef is an ideal ecosystem to explore the influence of natural environmental drivers on fluctuations in benthic cover and coral-algal interactions across a complete reef system.…”
Section: Introductionmentioning
confidence: 99%
“…Some coral species are able to maintain normal calcification rates across large natural acidification gradients (Fabricius et al, 2011;Shamberger et al, 2014;Barkley et al, 2015), indicative of adaptation or acclimation (Barkley et al, 2017). One potential mechanism to counteract acidification of surrounding seawater is pH homeostasis at the site of calcification (Georgiou et al, 2015;Barkley et al, 2017). Corals calcify from an isolated fluid located between the living tissue and the existing skeleton (Barnes, 1970;Cohen and McConnaughey, 2003;Venn et al, 2011;Tambutté et al, 2012).…”
Section: Introductionmentioning
confidence: 99%